Financial Incentives and Reproductive Health Behaviour: Evaluating the Impact of a BISP-Linked E-Voucher Program on Family Planning Uptake in South Punjab, Pakistan - Imran Ahmed; Sohail Anwar; An ul Abdin; Wajahat Yaqub (`, 2026)
Purpose: This study evaluates the effectiveness of the delivery of a family planning E-Voucher program as part of the largest social protection program in Pakistan, the Benazir Income Support Program (BISP), in increasing access to reproductive health services among poor populations. The objective of the research is to solve the problem of whether voucher utilization contributes towards family planning adoption among BISP beneficiary women in District Dera Ghazi Khan, and to find out the real contribution of behaviour and socio-culture in the reproductive health decision. Design/Methodology/Approach: A cross-sectional quantitative survey was conducted amongst 528 married reproductive age women registered as BISP beneficiaries. Data was collected with a structured questionnaire of the socio-demographic characteristics, voucher awareness and utilization, reproductive health knowledge, and contraceptive adoption behaviour. The techniques of descriptive statistics, logistic regression, mediation analysis, moderation analysis, and subgroup robustness tests were used to analyse how voucher utilization and family planning uptake are related. Findings: The results show that there is a significant association between the utilization of E-Voucher and the adoption of family planning (p<0.01), with a beta value of -0.600. However, the explanatory power of the regression models is small (Pseudo-R2c 0.012), suggesting financial incentives alone are not enough to explain reproductive health behaviour. Mediation analysis shows that knowledge improvement and voucher process awareness do not significantly transmit the effect of voucher utilization on contraceptive adoption, whereas in moderation analysis, cultural norms, household decision-making authority, and mobility constraints do not significantly modify the effect of voucher utilization on uptake. Subgroup analysis shows stronger effects of the voucher on female tribal and economically marginalized people. Implications/Originality/Value: The results indicate that demand-side financing interventions can bring improvements in access to reproductive health services, but that these interventions need to be combined with broader behavioural interventions and health system improvement if long-term reproductive health outcomes are to be achieved. Keywords: Family Planning Uptake; Demand-Side Financing; Health Voucher Programs; Benazir Income Support Program (BISP); Reproductive Health in Pakistan.